Recreational Pole Dancing in Lebanon - Chazbeck, Yara (2024)
Recreational pole dancing, distinct from pole dancing that takes place in gentlemen's strip clubs, is constructed as a fitness activity in gyms and dance studios, an art form, and a type of dancing that is no different than other forms of dancing using a prop. There has been an ongoing feminist debate on the nature of pole dancing; whether it is a sexualizing activity that objectifies women or whether it is an embodying experience that promotes sexual empowerment, autonomy, positive body image, and diversity. Due to its stigmatization and association with sex work, recreational pole dancing may create controversy in Arab countries. The activity may be perceived as "inappropriate" in conservative Arab societies. Therefore, this study aims to explore the nature of pole dancing in Lebanon through a gendered and cultural lens, applying a feminist qualitative methodology, and standpoint theory. Hence, semi-structured interviews were conducted with 7 pole dance practitioners in Lebanon to explore their lived experiences and investigate how pole dancing have impacted different aspects of their lives. This study indicates that recreational pole dancing is linked to an increased feeling of wellbeing, an expression of alternative femininities and masculinities, confidence, body-esteem, and attachment to an empowering pole community. The latter also act as the main motives for Lebanese polers’ participation in pole. Other findings include pole dancing impacting polers’ work life and relationships, in both positive and negative aspects. Finally, Lebanese polers report facing stigmatization, mainly degrading and sexualizing comments offline and online, losing friendships and compromised marriage prospects. Despite the stigma, polers actively chose to disclose their pole practice publicly and reeducate people’s sensibilities on seeing semi-naked bodies on a pole.